MOTIVASI KERJA PEGAWAI PADA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH PROVINSI SULAWESI TENGAH - Suangga, Yulistina (Katalogis, 2018)
This research used qualitative research method. It was conducted at Research and Development Body of Central Sulawesi Province with 7 informants drawn by applying purposive sampling. The data were collected through interview, observation and documentation. The data were analyzed by applying Domain analysis technique by Sugiono (2009:255), obtaining general and whole description from the research or social situation. The result of the research showed that the working motivation of the employees at Research and Development Body of Central Sulawesi Province was in the category of Good, it was proven by 3 aspects as what has been stated inÂ the theory of McClellend that achievement, power and affiliation are the sources of working motivation for the employees to do their duties and functions properly. The research proved that the employees had shown high motivation to work well with a hope to getÂ good acknowledgement from either the higher employees or their co-workers, as well as from power aspect, in which they had performed good working motivation which led to position or promotion and from affiliation aspect, in which the employees had shown good working motivation because the higher and the lower were cooperating together in achieving the vision and mission of Research and Development Body of Central Sulawesi Province.